2021
DOI: 10.1016/j.isci.2021.102431
|View full text |Cite
|
Sign up to set email alerts
|

Apoferritin improves motor deficits in MPTP-treated mice by regulating brain iron metabolism and ferroptosis

Abstract: HighlightsApoferritin improved MPTP-induced motor deficits.Apoferritin rescued dopaminergic neurodegeneration in the SN of MPTP-treated mice. Apoferritin inhibited MPTP-induced iron aggregation.Apoferritin prevented MPTP-induced ferroptosis by regulation of ACSL4 and FSP1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…Human brain imaging studies have shown that DFP decreases brain iron levels, alters cerebrospinal fluid ferritin, and mitigates dyskinesia ( Martin-Bastida et al, 2017 ). Similarly, both the blockage of ferritin degradation by ferritinophagy inhibitors chloroquine and bafilomycin A1 and the application of an iron-free form of ferritin, apoferritin, have been reported to chelate excess iron to protect DA neurons against PD ( Tian et al, 2020 ; Song et al, 2021 ). Moreover, NADPH oxidase inhibitor apocynin was also found to inhibit iron accumulation and lipid peroxidation, therefore ameliorating dopaminergic neurodegeneration and motor function abnormality in PD mice ( Hou et al, 2019 ).…”
Section: Emerging Links Of Ferroptosis To Neurodegenerative Diseasesmentioning
confidence: 99%
“…Human brain imaging studies have shown that DFP decreases brain iron levels, alters cerebrospinal fluid ferritin, and mitigates dyskinesia ( Martin-Bastida et al, 2017 ). Similarly, both the blockage of ferritin degradation by ferritinophagy inhibitors chloroquine and bafilomycin A1 and the application of an iron-free form of ferritin, apoferritin, have been reported to chelate excess iron to protect DA neurons against PD ( Tian et al, 2020 ; Song et al, 2021 ). Moreover, NADPH oxidase inhibitor apocynin was also found to inhibit iron accumulation and lipid peroxidation, therefore ameliorating dopaminergic neurodegeneration and motor function abnormality in PD mice ( Hou et al, 2019 ).…”
Section: Emerging Links Of Ferroptosis To Neurodegenerative Diseasesmentioning
confidence: 99%
“…Moreover, inhibition of the production of microglial proinflammatory cytokines and lipid peroxidation by knocking down acyl-CoA synthetase long-chain family member 4 (ACSL4) in an ischemic stroke model prevented ferroptosis in neurons [68]. Similar neuroprotective effects on ACSL4 were observed in the MPTP-induced PD model [69].…”
Section: Microgliamentioning
confidence: 76%
“…Our previous study demonstrates that the expression of divalent metal transporter 1 (DMT1) is increased with excessive iron deposition in injured spinal cord, and reduced DMT1 expression decreases iron accumulation with the treatment of deferoxamine [ 54 ]. Further evidence indicates that the upregulation of transferrin receptor 1 (TfR1) reduces iron accumulation with the application of apoferritin [ 55 ]. Hence, it is reasonable to believe that DPX reduces iron accumulation at perihematomal site that might ascribe to mediating the expression of DMT1 and TfR1 that is going to be investigated in our future research.…”
Section: Discussionmentioning
confidence: 99%